College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter 1 - Test - Page 167: 9



Work Step by Step

$$\sqrt{-2x+3}=3-\sqrt{x+3}$$ $$-2x+3=9-6\sqrt{x+3}+(\sqrt{x+3})^2$$ $$-2x+3=12-6\sqrt{x+3}+x$$ $$-3x-9=-6\sqrt{x+3}$$ $$x+3=2\sqrt{x+3}$$ Square both sides. $$x^2+6x+9=4(x+3)$$ $$x^2+6x+9=4x+12$$ $$x^2+2x-3=0$$ $$(x+3)(x-1)=0$$ $$x=1,-3$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.